Analysis of The Hadith That Women are Created from The Ribs: Theological Issues of Islamic Feminism - Hulisan, Muhammad Fasih (Pusat Studi Gender Universitas Jember, 2024)
One of the theological issues in Islam is the concept of human creation. Within the scope of the issue of human creation, there is also a discussion of the origin of the creation of women in the hadith. The Hadith about women being created from a rib is one of the theological issues in the issue of Islamic feminism. Therefore, this research is intended to find the location of problems related to the understanding of the hadith, then offer a new view in parsing the theological problems of Islamic feminism and try to produce a reconstruction of understanding of the hadith about women created from ribs. This research uses a qualitative method with a type of library research, accompanied by a hadith criticism approach. This research reveals that the wording of the hadith